2014
DOI: 10.4236/ojemd.2014.42003
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Endocrine Disorders in Thalassaemia

Abstract: Endocrine dysfunction in thalassaemia is amongst the most common complication and is principally attributed to excessive iron overload and suboptimal chelation. The prevalence is quite high particularly in multiethnic populations but determining the prevalence is often difficult due to the widespread heterogeneity of the population and timing of exposure to chelation therapy. Disturbances in growth, pubertal development, abnormal gonadal functions, impaired thyroid, parathyroid and adrenal functions, diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 72 publications
3
17
0
Order By: Relevance
“…The results of our study showed that height (short stature) and weight (weight failure ) of patients were signi icantly correlated with the Tanner stage (P=0.028 and P=0.007, respectively). Our results are similar to other studies done in other areas of the world like Heshmat Moayeri MD study in Tehran, Iran, and M. G. Vogiatzi study in North America (De et al, 2014). There are multifactorial pathogenesis explained growth failure in thalassemia and commonly iron accumulation due to frequent transfusion of blood and iron toxicity on endocrine gland (Puberty retardation, hypogonadism, GH de iciency, hypothyroidism, and diabetes), Side effect of chelating agents especially desferrioxamine, Another factors such as chronic anemia, hypersplenism, de iciency of folate, mineral such as Calcium and zinc (Vogiatzi et al, 2009).…”
Section: General Characteristics Of the Study Samplesupporting
confidence: 92%
“…The results of our study showed that height (short stature) and weight (weight failure ) of patients were signi icantly correlated with the Tanner stage (P=0.028 and P=0.007, respectively). Our results are similar to other studies done in other areas of the world like Heshmat Moayeri MD study in Tehran, Iran, and M. G. Vogiatzi study in North America (De et al, 2014). There are multifactorial pathogenesis explained growth failure in thalassemia and commonly iron accumulation due to frequent transfusion of blood and iron toxicity on endocrine gland (Puberty retardation, hypogonadism, GH de iciency, hypothyroidism, and diabetes), Side effect of chelating agents especially desferrioxamine, Another factors such as chronic anemia, hypersplenism, de iciency of folate, mineral such as Calcium and zinc (Vogiatzi et al, 2009).…”
Section: General Characteristics Of the Study Samplesupporting
confidence: 92%
“…[1][2][3][4][5] About 20-30% might have growth hormone deficiency and 80% might have very low growth hormone that were lower than would be expected for constitutional short stature. 6 In Indonesian thalassemia patients, 65% had short stature, 20% delayed puberty, 41% hypoparathyroidism, and 29% delayed bone age. 5 A previous study at Dr. Hasan Sadikin Hospital found that 67% of 10 to14-year-old patients had delayed growth.…”
mentioning
confidence: 99%
“…And hypogonadism is the most common endocrine complication in such patient [4]. There is evidence that hypogonadism can be due to primary gonadal failure as a puberty is also an important contributing factor to growth failure in adolescent, who do not exhibit a normal growth spurt [3,6,7]. Growth hormone deficiency is not a rare occurrence in adult thalassemic patients [8].…”
Section: Discussionmentioning
confidence: 99%
“…It has already been established that the iron overload is the prime cause of endocrinopathy in thalassemia [3]. And hypogonadism is the most common endocrine complication in such patient [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation